Design of patch antenna on LTCC substrate with broadband and high gain at millimetre wave band. Issue 25 (1st December 2013) - Kim, D.Y.; Jun, D.S.; Kang, D.M.; Lim, J.W.
Abstract : A new antenna structure with broadband and high gain at the millimetre wave bands is presented. This antenna consists of a conventional patch fabricated on a thick low‐temperature cofired ceramic (LTCC) substrate. By introducing an inner ground plane surrounding the main patch, the propagation of the surface wave is prevented, and antenna gain is increased. Furthermore, the bandwidth of this antenna becomes wider due to the coupling between the main patch resonator and the newly introduced dielectric resonator. The simulated results of the proposed antenna show a bandwidth and peak antenna gain at 60 GHz of 12 GHz and 9.4 dBi, respectively.